An Exercise to Introduce Power. (5th April 2011) - Seier, Edith; Liu, Yali
Summary In introductory statistics courses, the concept of power is usually presented in the context of testing hypotheses about the population mean. We instead propose an exercise that uses a binomial probability table to introduce the idea of power in the context of testing a population proportion.